Influence of Green Banking and Financial Performance Implementation to Profitability Levels in Conventional Banking Financial Companies Listed On the Indonesian Stock Exchange Period 2020 - Friyanto, Friyanto; Haritsar, Yosar (PT. Riset Press International, 2024)
The Interesting talks in the company in Indonesia is about social and environmental issues. This event corresponds to the publication of Presidential Regulation No. 92 of 2020 pertaining to the Ministry of Environment and Forestry. As a result, having complete and accurate environmental information will lead to better environmental performance. In this situation, financial services firms such as banks can help to realize a green environment by channeling financing to environmentally friendly and sustainable businesses. The purpose of this study was to analyze the effect of Green Banking and Financial Performance on the Level of Profitability in Conventional Bank Sector Financial Companies Listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 term. For a total sample of 21 enterprises, this study used the purposive sampling method and secondary data in the form of financial statements. SPSS 24.0 was used to analyze the data using the multiple linear regression analysis approach. The findings revealed that Green Accounting has a marginally (Test t) insignificant influence on Return On Asset (ROA). Return On Asset (ROA) is influenced by Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), BOPO, and Loan to Deposit Asset Ratio (LDR).